2004
DOI: 10.1088/0953-8984/16/31/025
|View full text |Cite
|
Sign up to set email alerts
|

Minority carrier properties of carbon-doped GaInAsN bipolar transistors

Abstract: We have developed an InGaP/GaInAsN/GaAs double heterojunction bipolar transistor technology that substantially improves upon existing GaAs-based HBTs. Band-gap engineering with dilute nitride GaInAsN alloys is utilized to enhance a variety of key device characteristics, including lower operating voltages, improved temperature stability and increased RF performance. Furthermore, GaInAsN-based HBTs are fully compatible with existing highvolume MOVPE and IC fabrication processes. While poor lifetimes have limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…[8][9][10][11][12][13][14] It is therefore very important that defects and impurities in these alloys are studied in detail. Carbon is a common impurity in various growth techniques 15,16 and sometimes, it is intentionally used as a p-type dopant; [17][18][19][20] complex formations between C and N could therefore be an important issue. Recently, Ulrici and Clerjaud 21 observed a sharp local vibration mode at 2087 cm −1 ͑at T =7 K͒ in GaP and a similar mode in GaAs.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] It is therefore very important that defects and impurities in these alloys are studied in detail. Carbon is a common impurity in various growth techniques 15,16 and sometimes, it is intentionally used as a p-type dopant; [17][18][19][20] complex formations between C and N could therefore be an important issue. Recently, Ulrici and Clerjaud 21 observed a sharp local vibration mode at 2087 cm −1 ͑at T =7 K͒ in GaP and a similar mode in GaAs.…”
Section: Introductionmentioning
confidence: 99%
“…Although these are very rough estimates, it is clear that 1) the observed µτ product varies with field, and 2) the ~0.1 V/µm fields observed in the best GaInNAs samples are expected to lead to field-aided collection. Evidence of field-aided minority-carrier transport in transistors has been reported by Welser, et al [14]. Aqueous junction In summary, we have observed that the device structure is more important than the growth conditions for high-performance GaInNAs cells.…”
Section: Modeled Solar-cell Performancesupporting
confidence: 73%
“…Therefore, the impact of base doping on minority carrier lifetime must be separated. These factors can be separated through the expression for average velocity where v is average velocity, N is average base doping, w is base width, and β is DC gain (9,10). The change in average velocity versus X L is plotted in Figure 2 for the three sets of dopant graded base layers, where X L is the thickness of the lower doped portion of the base adjacent to the collector (i.e.…”
Section: Resultsmentioning
confidence: 99%